Alcohol, drugs and young people: clinical approaches - Gilvarry, Eilish (Clinics in developmental medicine, 2007)
Policy : the principles of service organization and practice / Paul McArdle and Eilish Gilvarry -- Determinants of substance misuse / Paul McArdle -- Drug use in young people : short-term effects and long-term harms / Dan Lubman, Yvonne Bonomo and Murat Yücel -- Young people, substances and harm / Mandy Abbott, Fariah Khan and Eilish Gilvarry -- Trends in substance use and abuse in young people / Cecilia A. Essau and Peter Wennberg -- Substance use and psychiatric comorbidity in children and adolescents / Michael Farrell -- The effectiveness of universal youth substance abuse prevention programmes / David R. Foxcroft, Debby Allen and Lindsey Coombes -- Prevention of substance abuse : targeted approaches / Paul McArdle -- Treatment : course and outcome / Eilish Gilvarry and Giles Hayden -- Legal and ethical issues in the treatment of children and young people / Sarah Woolrich -- Principles of assessment for adolescents with substance use disorders / Oscar G. Bukstein and Theresa Lutka-Fedor -- Assessment instruments and outcome measurement / Oscar G. Bukstein and Theresa Lutka-Fedor -- Biological markers (drugs) / Kim Wolff -- Assessement and management in the emergency department and the paediatric unit / Joan Robson -- Brief alcohol interventions in young people : evidence and applicability / Malathi Natarajan and Eileen Kaner -- Psychological interventions for young people with substance misuse disorders / Gillian Tober -- Empirical and clinical foundations of family-based interventions for adolescent substance abuse / Howard A. Liddle, Cynthia L. Rowe and Gayle A. Dakof -- Pharmacological treatment of adolescent substance use disorder / E. Jane Marshall and K.A.H. Mirza -- The role of primary care in management of substance use/abuse / Clare Gerada -- Integrated treatment of substance use disorders and co-occurring psychiatric disorders in adolescents / Robert D. Davies and Paula D. Riggs